Spatial Association of Wetlands over Physical Variants in Barind Tract of West Bengal, India. - Rajeb Tarani Das; Swades Pal (Journal of Wetlands Environmental Management, 2016)
Abstract: Barind tract of west Bengal is an uplifted old alluvial plain area where only <1 percent area is covered by wetland. Present paper concentrates on general understanding of wetland association with different geographical settings like geological, geomorphological lithological structure and altitudinal gradations. Detail investigation reveals that geological and morphological structure do not have deep influence on wetland formation and their distribution in particular favourable sub-region. But altitudinal control on wetland is noticeable. An irregular distribution of wetland is found throughout the region because of multi parametric influence on it. In recent decades wetlands in barind tract has been undergoing into rapid loss. Continuous encroachment of agricultural field and newly built-up area to wetland are considered as main causes of wetland loss in barind tract.Â